Integrating human biomonitoring exposure data into a primary care morbidity database: a feasibility study - Pieter Jansen; Elly Den Hond; Katleen De Brouwere; Endale Alemayehu Ali; Hamid Yimam Hassen; Ilona Gabaret; Gijs Van Pottelbergh (Environmental Health)
Abstract Background The detection of a local per- and polyfluoroalkyl substances (PFAS) pollution hotspot in Zwijndrecht (Belgium) necessitated immediate action to address health concerns of the local community. Several human biomonitoring (HBM) studies were initiated, gathering cross-sectional exposure data from more than 10,000 participants. The linkage of these HBM data with primary care health registries might be a useful new tool in environmental health analysis. Aim We assessed the feasibility of linking exposure data from HBM programs to health outcomes from the Intego registry, which collects data from general practitioners’ electronic health records. This feasibility study uses exposure data from one of the completed PFAS HBM studies, which included 796 individuals. We describe the separate datasets, the process of integrating the HBM data into Intego, the analysis plan and the advantages and challenges of using this method. Results We established the integration of HBM data into the Intego primary care morbidity database, adhering to stringent privacy regulations and quality standards to ensure result integrity. Because of the modest sample size used in this feasibility study, no conclusions about the impact of PFAS on health endpoints can be drawn. However, with PFAS data from more than 10,000 residents available soon, more robust studies will be possible with this new method. Interpretation We introduce a novel approach for assessing the impact of environmental health hazards within primary care settings. The methods outlined here not only pave the way for larger-scale projects but also offer a promising avenue for long-term environmental health monitoring.